Loss of Cajal bodies in motor neurons from patients with novel mutations in VRK1. (2nd April 2019) - El-Bazzal, Lara; Rihan, Khalil; Bernard-Marissal, Nathalie; Castro, Christel; Chouery-Khoury, Eliane; Desvignes, Jean-Pierre; Atkinson, Alexandre; Bertaux, Karine; Koussa, Salam; Lévy, Nicolas; Bartoli, Marc; Mégarbané, André; et al.
Abstract: Distal hereditary motor neuropathies (dHMNs) are a heterogeneous group of diseases, resembling Charcot–Marie–Tooth syndromes, but characterized by an exclusive involvement of the motor part of the peripheral nervous system. Here, we describe two new compound heterozygous mutations in VRK1, the vaccinia-related kinase 1 gene, in two siblings from a Lebanese family, affected with dHMN associated with upper motor neurons (MNs) signs. The mutations lead to severely reduced levels of VRK1 by impairing its stability, and to a shift of nuclear VRK1 to cytoplasm. Depletion of VRK1 from the nucleus alters the dynamics of coilin, a phosphorylation target of VRK1, by reducing its stability through increased proteasomal degradation. In human-induced pluripotent stem cell-derived MNs from patients, we demonstrate that this drop in VRK1 levels leads to Cajal bodies (CBs) disassembly and to defects in neurite outgrowth and branching. Mutations in VRK1 have been previously reported in several neurological diseases affecting lower or both upper and lower MNs. Here, we describe a new phenotype linked to VRK1 mutations, presenting as a classical slowly progressive motor neuropathy, beginning in the second decade of life, with associated upper MN signs. We provide, for the first time, evidence for a role of VRK1 in regulating CB assembly in MNs . The observed MN defects are consistent with a length dependent axonopathy affecting lower and upper MNs, and we propose that diseases due to mutations in VRK1 should be grouped under a unique entity named `VRK1-related motor neuron disease'.